2022
DOI: 10.1080/19490976.2021.2020067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antibiotic pretreatment on bacterial engraftment after Fecal Microbiota Transplant (FMT) in IBS-D

Abstract: Fecal microbiota transplantation (FMT) is an attractive strategy to correct microbial dysbiosis in diarrhea-predominant irritable bowel syndrome (IBS-D). Although the mechanism of FMT is thought to be bacterial engraftment, the best approach to achieve engraftment after FMT in IBS-D (and other diseases) is not clear. We evaluated the effect of FMT (with or without pretreatment with antibiotics) on gut microbiome and symptoms in patients with IBS-D. In this randomized, placebo-controlled, single-center study, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 29 publications
0
57
1
Order By: Relevance
“…FMT is a critical technique for research into the functions of gut microbiota. 58 To further investigate whether the MFD affected early-life gut health by regulating the maternal gut microbiota, sow fecal microbiota was transplanted to broad-spectrum antibiotic-treated mouse dams. FMT from the MFD notably alleviated the LPS-induced decrease in α-diversity and gut Lactobacillus in both mouse dams and pups.…”
Section: Discussionmentioning
confidence: 99%
“…FMT is a critical technique for research into the functions of gut microbiota. 58 To further investigate whether the MFD affected early-life gut health by regulating the maternal gut microbiota, sow fecal microbiota was transplanted to broad-spectrum antibiotic-treated mouse dams. FMT from the MFD notably alleviated the LPS-induced decrease in α-diversity and gut Lactobacillus in both mouse dams and pups.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more and more animal experiments showed that gut microbiome interventions can treat or delay the disease ( Bermudez-Martin et al, 2021 ; Rao et al, 2021 ). Clinical trials found FMT to be effective for diarrhea-predominant irritable bowel syndrome ( Singh et al, 2022 ). Recently, FMT has also been used to treat membranous nephropathy as mentioned in a case report ( Zhou et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the antibiotics is to decrease the abundance of C. difficile load and to create space for the establishment of the transplanted donor microbes. Routine administration of oral antibiotics in the absence of active colitis is generally not recommended due to concerns of diminished efficacy, especially in patients with diarrhea-predominant irritable bowel disease, in which antibiotic pretreatment has been shown to significantly reduce bacterial engraftment [11]. Bowel preparation with two to three liters of oral polyethylene glycol with electrolyte purgative is carried out on the day prior to FMT.…”
Section: Steps and Biologic Effects Of Fmt 21 The Steps Of Fmtmentioning
confidence: 99%